2016
DOI: 10.1080/13691457.2016.1255591
|View full text |Cite
|
Sign up to set email alerts
|

Developing family-based care: complexities in implementing the UN Guidelines for the Alternative Care of Children

Abstract: This version is available at https://strathprints.strath.ac.uk/55518/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 14 publications
0
26
0
1
Order By: Relevance
“…The importance of localization within globalization has been very helpfully highlighted by the Guidelines for the Alternative Care of Children produced by the United Nations (2010). The Guidelines set out the implications for out-ofhome care of the United Nations Convention on the Rights of the Child (UNCRC; Cantwell, Davidson, Elsley, Milligan, & Quinn, 2014;Davidson, Milligan, Quinn, Cantwell, & Elsley, 2017). Global principles are asserted which are to be followed at national, local, and individual levels: out-of-home care must be genuinely needed (the "necessity principle, " Cantwell et al, 2014, p. 49), and when it is needed, it should be provided in an appropriate manner (the "suitability principle, " Cantwell et al, 2014, p. 66).…”
Section: Global Context Of Care-leavingmentioning
confidence: 99%
“…The importance of localization within globalization has been very helpfully highlighted by the Guidelines for the Alternative Care of Children produced by the United Nations (2010). The Guidelines set out the implications for out-ofhome care of the United Nations Convention on the Rights of the Child (UNCRC; Cantwell, Davidson, Elsley, Milligan, & Quinn, 2014;Davidson, Milligan, Quinn, Cantwell, & Elsley, 2017). Global principles are asserted which are to be followed at national, local, and individual levels: out-of-home care must be genuinely needed (the "necessity principle, " Cantwell et al, 2014, p. 49), and when it is needed, it should be provided in an appropriate manner (the "suitability principle, " Cantwell et al, 2014, p. 66).…”
Section: Global Context Of Care-leavingmentioning
confidence: 99%
“…In nearly all cases, caregivers do not provide warm, sensitive, and responsive interactions with children…. (McCall et al, p. 88, in Davidson et al, 2016, p. 2)…”
Section: What Is ‘Deinstitutionalisation’?mentioning
confidence: 98%
“…Further, quality of care is not assured by default in family-based care (as evidenced in the Rwanda case below), which is not a ‘perfect’ solution devoid of gaps and challenges as Davidson et al (2016) highlight, taking foster care as an illustration. They question: Children may be cared for in one family, but to whom do they look for their identity and in which long-term family will they live their adult life?…”
Section: What Is ‘Deinstitutionalisation’?mentioning
confidence: 99%
“…This movement acquired international visibility in 2009 with the passing of a UN resolution supporting guidelines for alternative care for children (Better Care Network, 2020; United Nations, 2009). Grounded in a concern for recognising children's rights and in research that has shown poor developmental outcomes for children raised in institutions, the UN guidelines reflect a global effort to redirect governmental and civil society support away from orphanages towards family‐based care (Davidson et al., 2017).…”
Section: From Orphanage To Family: the Global De‐institutionalisation Movementmentioning
confidence: 99%